Community-acquired urinary tract infections due to extended-spectrum β -lactamase-producing organisms in United Arab Emirates. Issue 22 (March 2018) - Ranjan Dash, Nihar; Albataineh, Mohammad T.; Alhourani, Nawar; Khoudeir, Ammar Mohammad; Ghanim, Mohammed; Wasim, Mohammad; Mahmoud, Ibrahim
Abstract: Background: The epidemiology of extended-spectrum β-lactamase (ESBL)-producing bacteria is fast evolving with increasing global trend towards community-acquired infections. Limited information available about ESBLs therapy outcomes and control strategies, especially in the Middle Eastern countries. Methods: We studied 399 ESBL-producing Escherichia coli and Klebsiella pneumoniae isolates from urinary tract infections (UTIs) occurred between 2014 and 2016 in University Hospital Sharjah. We included 124 ESBL-negative E. coli and K. pneumoniae isolates from UTIs as controls. Pearson Chi squares test and independent t -test were used to compare difference between ESBL positives and negatives. Multivariate logistic regression analysis was also performed. Results: Approximately 75% of the E. coli and K. pneumoniae isolates causing UTIs were community-acquired. We found that recurrent UTIs, old age, and catheterization among other risk factors for community-acquired ESBL-positive UTIs. Majority of these ESBL-positive isolates were resistant to antibiotics such as ciprofloxacin (74%) and trimethoprim-sulphamethoxazole (73%) that are commonly used for treatment of community-acquired urinary tract infections. Conclusions: ESBL-producing E. coli and K. pneumoniae have become major etiological pathogens of community-acquired UTIs in the United Arab Emirates. Healthcare providers should implement better infection control strategies and careful use of antimicrobials especially in out-patient and community settings.